Dangerous Women or Women in Danger? Women and Properties of Extinct Households in Late Imperial China - Sun Jiahong; Luca Gabbiani (L'Atelier du CRH)
Over its evolution, imperial China’s legal tradition has produced as series of laws and regulations on the issue of vacant successions, which were supplemented by a host of local practices or “customs”. This body of legal and customary rules had a profound impact on the rights of women to ownership, in a context in which there existed a profound cultural bias in favor of men. Even though social status and the role played in the family circle did account for some differentiation, fundamentally, it was all but impossible for women to be treated on an equal footing with men, especially with regard to assets’ inheritance. In fact, in the eyes of male family members, widows, daughters and daughters-in-law were often considered as threats to the integrity of a household’s properties. As numerous Qing dynasty judicial cases show, these “dangerous women” –especially widows– were regularly confronted to all sorts of pressures from the families to which they belonged, which could end up jeopardizing their material and physical well-being. Confronted with this category of “endangered women”, in time state authorities devised legal tools and highly symbolic gestures in order to provide some form of protection for them.